Does the Pre-Open Auction Market Improve Efficiency of Price Discovery in Stock Markets? Evidence from India - Sharma, Gagan Deep; Gupta, Mansi (Indian Journal of Finance, 2015)
The paper analyzed the impact of opening call auction on the efficiency of price discovery at the National Stock Exchange (NSE), India by studying the returns and volatility behavior of one benchmark index (NSE’s Nifty) and 10 Nifty component companies selected on random. The paper used the closing prices for the period 3 years before and 3 years after the introduction of the call auction market in 2010. Descriptive statistics, one-way ANOVA, augmented Dickey-Fuller unit-root Test, and ARCH-GARCH type methodology was employed for the analysis. The paper found no significant difference in the returns during the two periods, though a reduction in volatility was observed. The introduction of the pre-open auction market resulted in an improvement in the efficiency of price discovery of various stocks. The findings of the paper offer valuable inputs for stock market regulators as well as investors.